ACTIVATION OF METALLIZED COLLOIDAL SOLUTIONS - Морозов, Андрей (SWorldJournal, 2022)
activating such a system by external oscillations. Therefore, there is an urgent task of analyzing the predicted behavior of metal particles in the acoustic processing of the dispersion medium.